THE INTERACTION OF LABOR MARKET AND MARKET EDUCATIONAL SERVICES - D. Bottaeva (Вестник университета, 2019)
The article is devoted to revealing the specifics of the interaction between labor market and market of educational services. The article presents the main features of this interaction and the factors of influence of competence-based approach on the effectiveness of the training of skilled graduates. Special attention is paid to ensuring that the competencies of students in accordance with the needs of employers in the changing conditions of the modern labor market. The article presents the basic concepts of representatives of different schools on the theme of supply and demand in the labor market.